PENGARUH PENGUKUSAN PADA EMPAT JENIS KAYU KERING UDARA TERHADAP IMPREGNASI DENGAN BAHAN PENGAWET CCA - Barly Barly; Pipin Permadi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Impregnation under pressure is the most effective way of applying preservative to timbers, but not all species can be treated effectively using the method. Air-dried timbers of 5 cm x 5 cm x 100 cm in dimension were impregnated with preservative used for constructional purposes. Part of wood samples was presteamed. Prior to the preservative treatment both groups were reconditioned to the same moisture content as the reference material (air dried).Retention and penetration figures have increased as presteaming was applied. The result revealed that two timbers preserved met the standard requirement. The preservation schedule proposed for the timbers is presented in this paper.